Determination of Culm Age in Bamboo - Khan, M. A. Waheed (Indian Forester, 1962)
In an intensively managed bamboo forest, it is necessary to know the age of individual culms, say upto 4 years, for judicious selection fellings. Culm age can be determined by studying differential morphological characters relating to culm-sheath, branches and culm itself. Though, these characters may vary to some extent according to the climatic features of a locality and the developmental stage of the clump itself, fair generalisations may, however, be made for any individual locality and accordingly an attempt has been made to evolve such distinguishing characters for 14 different species of bamboos, both indigenous and exotic, as are growing in the Forest Research Institute, Dehru Dun. Photographic illustrations are also provided.